Pelatihan Guru TK dalam Pengembangan Media Belajar Daur Ulang Berbasis Budaya Lokal - Diana; Ahmad Faisal Amri; Hanum Mukti Rahayu; Pipin Septiani; Dhea Muliana (BALE LITERASI, 2026)
Early childhood teachers play an important role in instilling character, creativity, and environmental awareness from an early age. However, many Aisyiyah kindergarten teachers in Pontianak still find it difficult to develop creative, environmentally friendly, and locally-based learning media. This community service activity aims to improve teachers' skills through training in the creation of recycled learning media based on the Pancasila Student Profile Strengthening Project (P5). The implementation methods include needs identification, concept and practice training, mentoring, and evaluation of results. The activity was held on October 14, 2025, at Aisyiyah 3 Kindergarten in Pontianak, attended by 42 ABA kindergarten teachers. Teachers used materials such as coconut leaves, coconut husks, corn husks, and ice cream sticks to create media themed on West Kalimantan culture, such as traditional houses and headdresses. The results showed an increase in teachers' skills and creativity, with 90% of participants able to produce ready-to-use media.